Hydro-mechanical behavior from small strain to failure of tuffs amended with dune sand – Application to pavements design in Saharan areas. (22nd February 2021) - Daheur, Elhadj Guesmia; Taibi, Said; Goual, Idriss; Li, Zhong-Sen
Highlights: The valorization of local material satisfies the design standards of Saharan roads. Significant increase in stiffness according to suction. The elastic modulus increases by a factor of 10 between wet and dry states. Capillary cohesion is strongly influenced by the variation in water content. Abstract: In the context of valorizing local materials at Saharan region for road constructions, a mixture composed of 65% tuff and 35% dune sand (named 65T35DS) was previously studied. The 65T35DS was shown to have the optimum geotechnical and mechanical properties. As an extension, this study consists in investigating the behavior of the 65T35DS mixture under coupled hydro-mechanical loadings. Suction-controlled drying-wetting tests were performed on the 65T35DS statically compacted at the modified Proctor optimum (MPO) state. A series of small-strain cyclic triaxial tests under constant water content condition was then followed. Key findings of this paper include i) the 65T35DS prepared at MPO state is able to resist severe drought condition without inducing significant shrinkage. However, it swells during wetting and the swelling indices are quantified by correlations; ii) the elastic modulus under small-strains is governed by suction and the applied confining stress. The effect of confining stress becomes dominant at lower suction level and negligible when suction increases; iii) at failure, the apparent cohesion drops quickly on the dry side of the MPO, on wet side, it decreases a little. The apparent friction angle decreases for the specimens with water content larger than 5.5%, i.e. wMPO – 5. The studied mixture satisfies the design standards of Saharan pavements and seems to be a good compromise for the valorization of local materials.